2011
DOI: 10.1097/mcg.0b013e318203dfb3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transjugular Intrahepatic Portosystemic Shunt (TIPS) Alone Versus TIPS Combined With Embolotherapy in Advanced Cirrhosis

Abstract: The results suggest that TIPS with embolotherapy cannot reduce the risk of rebleeding if PPG is less than 12 mm Hg after TIPS. PPG after TIPS is an independent predictor of rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…The group of TIPS with surgical portal azygous disconnection was further excluded from our meta‐analysis . Thus, a total of six articles were included in our meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The group of TIPS with surgical portal azygous disconnection was further excluded from our meta‐analysis . Thus, a total of six articles were included in our meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…The type of stents was covered stent alone in two studies, bare stent alone in two studies, both bare and covered stent in one study, and unknown in one study . Varices were angiographically embolized by coils with or without liquids agents in all studies . Liquids agents were employed in three studies, including α‐cyanoacrylate ( n = 1), ethanol ( n = 1), and sclerosing agents ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis reported that patients with TIPS + variceal embolization had significantly lower rebleeding (OR=2.02, P=0.002) but similar incidences of shunt dysfunction, HE, and death than patients with TIPS alone (40). Furthermore, Xiao et al (41) found no difference in incidence of rebleeding, shunt revision, encephalopathy, and overall survival in patients with portosystemic gradient ≤12 mmHg after stent implantation and angioplasty. However, portosystemic gradient after TIPS placement was an independent predictor of rebleeding (P=0.036).…”
Section: Discussionmentioning
confidence: 97%